Expressing the Pro-Apoptotic Reaper Protein via Insertion into the Structural Open Reading Frame of Sindbis Virus Reduces the Ability to Infect Aedes aegypti Mosquitoes - Alexis Carpenter; Scott R. Santos; Rollie J. Clem (Viruses, 2022)
Arboviruses continue to threaten a significant portion of the human population, and a better understanding is needed of the determinants of successful arbovirus infection of arthropod vectors. Avoiding apoptosis has been shown to be one such determinant. Previous work showed that a Sindbis virus (SINV) construct called MRE/rpr that expresses the Drosophila pro-apoptotic protein Reaper via a duplicated subgenomic promoter had a reduced ability to orally infect Aedes aegypti mosquitoes at 3 days post-blood meal (PBM), but this difference diminished over time as virus variants containing deletions in the inserted reaper gene rapidly predominated. In order to further clarify the effect of midgut apoptosis on disseminated infection in Ae. aegypti, we constructed MRE/rprORF, a version of SINV containing reaper inserted into the structural open reading frame (ORF) as an in-frame fusion. MRE/rprORF successfully expressed Reaper, replicated similarly to MRE/rpr in cell lines, induced apoptosis in cultured cells, and caused increased effector caspase activity in mosquito midgut tissue. Mosquitoes that fed on blood containing MRE/rprORF developed significantly less midgut and disseminated infection when compared to MRE/rpr or a control virus up to at least 7 days PBM, when less than 50% of mosquitoes that ingested MRE/rprORF had detectable disseminated infection, compared with around 80% or more of mosquitoes fed with MRE/rpr or control virus. However, virus titer in the minority of mosquitoes that became infected with MRE/rprORF was not significantly different from control virus. Deep sequencing of virus populations from ten mosquitoes infected with MRE/rprORF indicated that the reaper insert was stable, with only a small number of point mutations and no deletions being observed at frequencies greater than 1%. Our results indicate that expression of Reaper by this method significantly reduces infection prevalence, but if infection is established then Reaper expression has limited ability to continue to suppress replication.